Synaptic and cellular plasticity in Parkinson’s disease - Chu Hong-Yuan (Acta Pharmacologica Sinica, 2020)
Parkinson’s disease (PD) is a progressive neurodegenerative disease, which causes a tremendous socioeconomic burden. PD patients are suffering from debilitating motor and nonmotor symptoms. Cardinal motor symptoms of PD, including akinesia, bradykinesia, resting tremor, and rigidity, are caused by the degeneration of dopaminergic neurons in the substantia nigra pars compacta. In addition, decreased amounts of dopamine (DA) level in the basal ganglia induces numerous adaptive changes at the cellular and synaptic levels in the basal ganglia circuits. These cellular and synaptic adaptations are believed to underlie the emergence and propagation of correlated, rhythmic pattern of activity throughout the interconnected cortico-basal ganglia-thalamocortical network. The widespread pathological pattern of brain activity is closely linked to the devastating motor symptoms of PD. Accumulating evidence suggests that both dopaminergic degeneration and the associated abnormal cellular and circuit activity in the basal ganglia drive the motor symptoms of PD. In this short review I summarize the recent advances in our understanding of synaptic and cellular alterations in two basal ganglia nuclei (i.e. the striatum and the subthalamic nucleus) following a complete loss of DA, and in our conceptual understanding of the cellular and circuit bases for the pathological pattern of brain activity in parkinsonian state.